The rural areas - the unutilized potential in light of tourism - Jana Jarábková (Agricultural Economics (AGRICECON), 2010)
The rural areas represent an extensive territorial or natural, human and economic potential which is utilized unevenly and imperfectly. One of the alternatives of using this potential is to develop tourism in those municipalities, which have appropriate conditions for the development of activities connected to tourism at their disposal. The aim of this paper is to identify the development potential of rural municipalities in the light of tourism (in the area of the Nitra Self-governing Region), to evaluate this potential using the valorisation method and to define the individual categories of rural municipalities. The results of the typology provide important information about the potential of the rural areas for the development of tourism and about the current utilization of this potential. They are also used to create the concept of the development of rural tourism in the Nitra Self-governing Region and to represent a tool for effectively allocated public resources for municipalities and for entrepreneurial subjects in the municipalities.